Pengaruh Parameter Geoteknik Hasil Pengeboran terhadap Desain Tambang di PT. Insani Baraperkasa, Kutai Kartanegara - Rahmat Rahman; Albertus Juvensius Pontus; Agus Winarno (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Mining with an open pit system is carried out by excavating and removing the overburden to obtain coal. However, before mining, it is important to obtain geotechnical data information. As well as the lithology of the rocks below the surface, it is necessary to carry out geotechnical drilling (full coring). This study can determine the value of slope geometry safety factors and plan safe slope geometry, both individual slopes and overall slopes. Therefore, this was done to determine the influence of GSI geotechnical parameters on the value of static and dynamic slope safety factors. The method used in determining the safety factor and the probability of an avalanche is the Morgenstern-Price boundary equilibrium method with the Generalized Hoek-Brown collapse criterion in static and dynamic slope conditions. The input parameters used in the analysis were natural density, compressive strength value (UCS), geological srength index (GSI), disturbance factor (D), intact rock constant (mi), as well as seismic load factor, and groundwater level. The optimal geometry on the Highwall slope is the configuration of the Highwall slope with a height of 74 m and an angle of 23°, supported by a single slope of 5-10 meters, a berm of 7 meters with an angle of 40°. Seam D Claystone lithology with GSI 50, Siltstone with GSI 70, Sandstone with GSI 70, and Seam E Claystone lithology with GSI 50, Siltstone with GSI 40, Sandstone with GSI 75.Can be applied within a safe limit where FK Static 1.7 PK Static 0% and FK Dynamic 1.4 PK Dynamic 6%.